2020
DOI: 10.1002/onco.13626
|View full text |Cite
|
Sign up to set email alerts
|

Implementing DPYD*2A Genotyping in Clinical Practice: The Quebec, Canada, Experience

Abstract: Background Fluoropyrimidines are used in chemotherapy combinations for multiple cancers. Deficient dihydropyrimidine dehydrogenase activity can lead to severe life‐threatening toxicities. DPYD*2A polymorphism is one of the most studied variants. The study objective was to document the impact of implementing this test in routine clinical practice. Methods We retrospectively performed chart reviews of all patients who tested positive for a heterozygous or homozygous DPYD*2A mutation in samples obtained from pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…The joint research with these early adopters enabled the optimization of diagnostic processes. This was actually reflected by our TAT analysis showing that DPYD testing results can be reliably returned in due time, i.e., without causing treatment delays, which is crucial for sustainable implementation ( Henricks et al, 2018 ; Jolivet et al, 2021 ).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…The joint research with these early adopters enabled the optimization of diagnostic processes. This was actually reflected by our TAT analysis showing that DPYD testing results can be reliably returned in due time, i.e., without causing treatment delays, which is crucial for sustainable implementation ( Henricks et al, 2018 ; Jolivet et al, 2021 ).…”
Section: Discussionmentioning
confidence: 67%
“…For three cases, it took more than 7 days (five working days) to report the result including an average “time to lab” of 2.0 days (range 0–7 days) and an “internal TAT” of 1.1 day (range 0–6 days). A TAT of 7 days is considered to be adequate to avoid therapy delays ( Henricks et al, 2018 ; Hamzic et al, 2020 ; Varughese et al, 2020 ; Jolivet et al, 2021 ). For the 97 requests indicating a planned therapy start, 77.3% of the reports ( n = 75) were returned to the ordering institution before planned therapy start or on the same day.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…57 Reported experience of systematic DPYD genotyping in routine practice showed that the administration of 5-FU at a reduced dose in patients heterozygous for DPYD*2A is safe. 58 There are also reported cases of severe toxicity (grade 3/4) induced by capecitabine that were found to be DPD deficient, 59 and DPYD genotyping successfully reduced this risk in a prospective study for breast cancer patients. 60 Variability in the genotype-phenotype relationship can be due to the regulation of DPD at the post-transcriptional level.…”
Section: Dpyd Genotypingmentioning
confidence: 99%
“…9 Finally, I agree that turnaround time is critical; real-world data from Quebec, Canada, indicate an average turnaround time of 6 days, with 99% of physicians reporting no significant treatment delays. 10 I also agree with Dr Hochster 1 that practitioners will inevitably encounter patients with complete loss of DPD activity. However, I would argue that the dire consequences are not medicolegal for practitioners but rather severe toxicity and death for those patients who receive full-dose fluoropyrimidine treatment.…”
mentioning
confidence: 62%